Stress-induced nuclear accumulation is dispensable for Hog1-dependent gene expression and virulence in a fungal pathogen. Issue 1 (December 2017) - Day, Alison; Herrero-de-Dios, Carmen; MacCallum, Donna; Brown, Alistair; Quinn, Janet
Abstract Stress-activated protein kinase (SAPK) pathways are evolutionarily conserved eukaryotic signalling modules that are essential for the virulence of human pathogenic fungi. The Hog1 SAPK inCandida albicans is robustly phosphorylated in response to a number of host-imposed stresses, and is essential for virulence. The current dogma is that stress-induced phosphorylation activates the SAPK, and promotes its nuclear accumulation that is necessary for the expression of SAPK-dependent stress-protective genes. Here we challenge this dogma.C .albicans strains were constructed in which Hog1 was either tethered to the plasma membrane or constitutively nuclear. Strikingly, tethering Hog1 to the plasma membrane did not abrogate stress resistance or stress-induced gene expression. Furthermore, preventing the nuclear accumulation of Hog1 had no impact onC .albicans virulence in two distinct models of systemic infection. However, tethering Hog1 to the plasma membrane did impact on signal fidelity, and on the magnitude and kinetics of the stress-induced phosphorylation of this SAPK. Taken together, these findings challenge the dogma that nuclear accumulation of SAPKs is a pre-requisite for SAPK-dependent gene expression, and reveal that stress-induced nuclear accumulation of Hog1 is dispensable for the virulence of a major human fungal pathogen.